Correlation between Stress Level and Hair Loss in Students - Nadira Sabrina Mufti; Wahyu Lestari; Sitti Hajar; RM Agung Pranata Kusuma Atmaja (Berkala Ilmu Kesehatan Kulit dan Kelamin (Periodical of Dermatology and Venerology))
Background: Hair loss is one of the most commonly reported problems in dermatology One of the causes of hair loss is high stress levels. The effects of stress can impact hair condition, which in turn can affect appearance. Purpose: This study was to determine the relationship between stress levels and the incidence of hair loss among students at Syiah Kuala University. Methods: This research employed an observational analytic study using approach, utilizing cross-sectional data. The number of subject used in this study was 100 students who were taken by the simple random sampling method. The data analysis used was bivariate analysis to see the relationship between stress levels and the incidence of hair loss. Result: Out of 100 subjects of students with normal, mild, moderate, severe, and very severe stress levels, 59% of them experienced pathological hair loss. By using a significance value of 95%, the relationship between stress levels and the incidence of hair loss in Syiah Kuala University students showed a significance value, or p-value, of 0.024. Conclusion: This study shows that there is a relationship between stress levels and the incidence of hair loss among students at the University of Syiah Kuala.